2019
DOI: 10.1007/s00455-019-10034-9
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Translational Value of Mouse Models of ALS for Dysphagia Therapeutic Discovery

Abstract: The goal of this study was to compare dysphagia phenotypes in low and high copy number (LCN and HCN) transgenic superoxide dismutase 1 (SOD1) mouse models of ALS to accelerate the discovery of novel and effective treatments for dysphagia and early amyotrophic lateral sclerosis (ALS) diagnosis. Clinicopathological features of dysphagia were characterized in individual transgenic mice and age-matched controls utilizing videofluoroscopy in conjunction with postmortem assays of the tongue and hypoglossal nucleus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 67 publications
3
25
0
Order By: Relevance
“…Swallowing function was also assessed every other week (the day after plethysmography) by using a VFSS protocol described in detail elsewhere. 20,30,31 Briefly, the night before testing, mice were water restricted for *14 h to encourage their willingness to drink while in the fluoroscope. A custom-designed, translucent/radiolucent, polycarbonate VFSS test chamber was added to the home cage overnight to allow acclimation.…”
Section: Videofluoroscopic Swallow Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Swallowing function was also assessed every other week (the day after plethysmography) by using a VFSS protocol described in detail elsewhere. 20,30,31 Briefly, the night before testing, mice were water restricted for *14 h to encourage their willingness to drink while in the fluoroscope. A custom-designed, translucent/radiolucent, polycarbonate VFSS test chamber was added to the home cage overnight to allow acclimation.…”
Section: Videofluoroscopic Swallow Studymentioning
confidence: 99%
“…We have previously used VFSS to assess a variety of swallowing metrics and have shown that end-stage MT mice have significantly slower lick and swallow rates compared with WT mice. 20,24,25 MT mice also lose weight rapidly as they approach end stage, and it would be logical to hypothesize that this is due, at least in part, to an impaired ability to ingest calories.…”
Section: Swallowing Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we investigated the stereotypical oropharyngeal deglutitive behavior of mice before and after MT versus MMB transection, evaluated using our previously validated videofluoroscopic swallow study (VFSS) methodology. 39,40,43,62 Based on our previous work, we expected VFSS outcome measures would be altered in a predictable direction: MT injury would result in slower lick and swallow rates, longer inter-swallow intervals, and greater lick-swallow ratios (i.e., vallecular fill time), collectively indicative of oropharyngeal (i.e., oral and pharyngeal stage) dysphagia; MMB injury would result solely in slower lick rate (i.e., oral stage dysphagia). Although we expected that MT transection would produce a more robust model for translational investigations of dysphagia treatment discovery, we recognize the potential benefits of establishing an MMB injury model: elimination of morbidity associated with impaired eye blink and vibrissae movement and confounding stress-induced responses associated with frequent daily handling for application of ocular lubricant.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these differences, both species use the tongue, jaw, and other oral cavity structures to facilitate the oral (i.e., preparatory or transport stage) and pharyngeal stages of swallowing and are presumed to utilize common neural substrates (Lever, Brooks, et al, ; Sang & Goyal, ). In fact, videofluoroscopic swallow studies have been used to document dysphagia in rodent models of amyotrophic lateral sclerosis (Lever, Braun, et al, ; Osman et al, ) and presbyphagia (Lever, Brooks, et al, ). The affected swallow metrics identified in these studies suggest that the swallowing mechanism is sufficiently similar between the two species and can be used in future investigations examining the neurologic pathways responsible for swallow function.…”
Section: Introductionmentioning
confidence: 99%